A long-term assessment of ecological-economic sustainability of woody biomass production in Japan. (1st February 2015) - Ooba, Makoto; Hayashi, Kiichiro; Fujii, Minoru; Fujita, Tsuyoshi; Machimura, Takashi; Matsui, Takanori
Abstract: The forestry process in Japan, from plantation stage to wood biomass production, was assessed using a process-based ecological model, forestry cost calculation model, and an ecological footprint-like index. In order to estimate ecosystem dynamics under various forest management practices, the ecosystem model simulated material cycles. The cost calculation model estimated the economic cost for each stage of woody biomass (wood chip) production. An occupancy rate time index (ORT) was defined by a 200-year usage span for land, material, pollution and labor against the amount available for woody biomass production. The models and the index were combined and four forest management scenarios were evaluated on a community scale in Japan: business as usual (BAU), a forest management recommended by the local government to enhance and improve forest management to include woody biomass production; FM1, modified practices; FM2, extended practices; and CNV, converting part of a plantation into natural broadleaf forest under the FM2 scenario, considering the biodiversity of the forests. The results for long-term simulations revealed that the current forest management (BAU and FM1) was not efficient in the production of woody biomass in terms of economic cost and ORT. The FM2 scenario modified from the FM1 scenario would produce ecological and economical improvements, but integrated assessment by using ORT indicated an increase in carbon emissions and labor due to enhanced forest practices. Woody biomass production under the FM2 scenario needs to be supported by carbon offsetting, such as reduction of coal combustion in thermal power plants. Under the CNV scenario, ORT values were the same as those under BAU and FM1 if the carbon offset was considered. The CNV scenario was found to be the best, considering the impact on ecological and social systems.